Manajemen Keuangan atau Pembiayaan Pendidikan - Sukatin, Sukatin; Rukmanah, Siti; Rosanti, Rosanti; Karim, Hafizul (Pedagogika: Jurnal Ilmu-Ilmu Kependidikan, 2023)
Education financing management is an important aspect in providing quality education. The main goal is to optimize the use of limited financial resources to meet educational needs effectively and efficiently. Financing management includes the process of budget planning, fund allocation, budget implementation, supervision, as well as evaluation and reporting. The main activities in education financing management include identifying funding sources, calculating operational and investment cost requirements, preparing budget plans, managing cash flow, making appropriate expenditures, and monitoring and evaluating budget use. Effective financing management requires careful planning, transparency, accountability and coordination between stakeholders. This aims to ensure the allocation of funds is fair, efficient and aligned with educational priorities. With good financing management, educational institutions can provide quality services and create a conducive learning environment for all students.